2020
DOI: 10.1126/sciadv.aay2042
|View full text |Cite
|
Sign up to set email alerts
|

Pumping mechanism of NM-R3, a light-driven bacterial chloride importer in the rhodopsin family

Abstract: A newly identified microbial rhodopsin, NM-R3, from the marine flavobacterium Nonlabens marinus, was recently shown to drive chloride ion uptake, extending our understanding of the diversity of mechanisms for biological energy conversion. To clarify the mechanism underlying its function, we characterized the crystal structures of NM-R3 in both the dark state and early intermediate photoexcited states produced by laser pulses of different intensities and temperatures. The displacement of chloride ions at five d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 50 publications
2
11
2
Order By: Relevance
“…The negative difference electron density and 2 F obs – F calc electron density features along Arg95 show that the side chain of Arg95 is disordered by the loss of hydrogen-bonding interactions. The similar disordering of Arg95 was seen in low temperature studies of NM-R3 in SR and TR-SFX experiments with KR2 (corresponding to Arg109 in KR2) at 1 ms following photoactivation (24, 31). The equivalent arginine residue is presumedly involved in the ion transfer in bR and Np HR (38, 39).…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…The negative difference electron density and 2 F obs – F calc electron density features along Arg95 show that the side chain of Arg95 is disordered by the loss of hydrogen-bonding interactions. The similar disordering of Arg95 was seen in low temperature studies of NM-R3 in SR and TR-SFX experiments with KR2 (corresponding to Arg109 in KR2) at 1 ms following photoactivation (24, 31). The equivalent arginine residue is presumedly involved in the ion transfer in bR and Np HR (38, 39).…”
Section: Resultssupporting
confidence: 70%
“…However, no difference electron density peaks are detected around these locations, and thus they are not a major position for I - at the time points but may instead indicate part of an anion transport pathway. Low temperature trapping studies of NM-R3 have shown that an electron density peak of bromide ion is observed around Cys105, Leu107, and Leu108 in helix C (24). In addition, low temperature trapping studies of Np HR have suggested that a bromide ion is displaced to a temporal cavity between the PSB and the side chain of Ile134 (corresponding to Leu106 of helix C in NM-R3) (37).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Crystal structures of ClR were previously determined with crystals under continuous illumination of visible laser light. Intriguingly, these steady-state models revealed unexpected movement of the retinal, without indication of photo-isomerization ( 22 ). Steady-state measurements, which show averages of mixed states, are thus of limited use in deciphering the molecular mechanism of light-driven Cl − pumping.…”
mentioning
confidence: 97%